2014
DOI: 10.1016/j.acalib.2014.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Factors that Increase the Probability of a Successful Academic Library Job Search

Abstract: Finding a position in an academic library can be challenging for recent Library and Information Science (LIS) graduates. While LIS students are often encouraged to seek out experience, network, and improve upon their technology skills in hopes of better improving their odds in the job market, little research exists to support this anecdotal advice. This study quantifies the academic and work experiences of recent LIS graduates in order to provide a better understanding of what factors most significantly influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…The research literature on entry-level professional library employment in the USA (Reeves and Hahn, 2010;Sproles and Ratledge, 2004;Eckard et al, 2014;Reed et al, 2015) has established the need for LIS graduates to obtain practical library experience before seeking library employment. Reeves and Hahn (2010) stress the importance of library employment in remaining competitive in a difficult entry-level job market:…”
Section: Discussionmentioning
confidence: 99%
“…The research literature on entry-level professional library employment in the USA (Reeves and Hahn, 2010;Sproles and Ratledge, 2004;Eckard et al, 2014;Reed et al, 2015) has established the need for LIS graduates to obtain practical library experience before seeking library employment. Reeves and Hahn (2010) stress the importance of library employment in remaining competitive in a difficult entry-level job market:…”
Section: Discussionmentioning
confidence: 99%
“…Instruction is emerging as an important concentration within the profession of librarianship (Lynch and Smith, 2001; Ashmore, 2002; Hall, 2013; Eckard et al , 2014; Julien et al , 2018). In the past four decades, the prevalence of instructional duties in library position descriptions has increased dramatically.…”
Section: Instruction In Librarianshipmentioning
confidence: 99%
“…Max Eckard found that candidates who had been employed in academic libraries were five times more likely to get a job compared to those who had not. 7 Furthermore, candidates who had participated in an internship or practicum were three times more likely to be successful on the job hunt.…”
Section: Gain Relevant Library Experience: Maximize Your Lis Degreementioning
confidence: 99%
“…A study found that factors such as prior academic library experience (including practicums), professional service/committee work, and a record of publications can significantly increase or decrease the odds of getting a job after graduation. 1 Brian Kenney suggests that LIS candidates can significantly increase their chances of landing a job by being willing to relocate and by effectively marketing themselves. 2 To be successful, a candidate needs to understand that the main purpose of the recruitment process is to assess the competency, fit and motivation of the candidate.…”
mentioning
confidence: 99%